Sebocytes contribute to skin inflammation by promoting the differentiation of T helper 17 cells. (1st March 2018) - Mattii, M.; Lovászi, M.; Garzorz, N.; Atenhan, A.; Quaranta, M.; Lauffer, F.; Konstantinow, A.; Küpper, M.; Zouboulis, C.C.; Kemeny, L.; Eyerich, K.; Schmidt‐Weber, C.B.; et al.
Summary: Background: The main function of sebocytes is considered to be the production of lipids to moisturize the skin. However, it recently became apparent that sebocytes release chemokines and cytokines and respond to proinflammatory stimuli as well as the presence of bacteria. Objectives: To analyse the functional communication between human sebocytes and T cells. Methods: Immunofluorescence stainings for CD4 and interleukin (IL)‐17 were performed on acne sections and healthy skin. Migration assays and T‐cell‐stimulation cultures were performed with supernatants derived from unstimulated or prestimulated SZ95 sebocytes. Dendritic cells were generated in the presence of SZ95 supernatant and subsequently used in mixed leucocyte reactions. Results: We showed that CD4 + IL‐17 + T cells accumulate around the pilosebaceous unit and are in close contact with sebocytes in acne lesions. By using SZ95 sebocyte supernatant, we demonstrate a chemotactic effect of sebocytes on neutrophils, monocytes and T cells in a CXCL8‐dependent manner. Furthermore, sebocyte supernatant induces the differentiation of CD4 + CD45RA + naive T cells into T helper (Th)17 cells via the secretion of IL‐6, transforming growth factor‐β and, most importantly, IL‐1β. No direct effects of sebocytes on the function of CD4 + CD45RO + memory T cells were detected. Moreover, sebocytes functionally interact with Propionibacterium acnes in the maturation of dendritic cells, leading to antigen‐presenting cells that preferentially prime Th17 cells. Conclusions: Our study provides evidence that human sebocytes actively participate in inflammatory processes in the skin by recruiting and communicating with immune cells. This interaction leads to the generation of Th17 cells, which might contribute to the pathogenesis not only of acne vulgaris, but also of several inflammatory skin diseases.